Linezolid Resistance in Enterococcus faecalis Associated With Urinary Tract Infections of Patients in a Tertiary Hospitals in China: Resistance Mechanisms, Virulence, and Risk Factors - Ma, Xiaoyu; Zhang, Fan; Bai, Bing; Lin, Zhiwei; Xu, Guangjian; Chen, Zhong; Sun, Xiang; Zheng, Jinxin; Deng, Qiwen; Yu, Zhijian (Frontiers in Public Health, 2021)
Background:Enterococcus faecalis has been commonly considered as one of the major pathogens of the urinary tract infection (UTI) in human host worldwide, whereas the molecular characteristics of E. faecalis clinical isolates from the patients with UTI in China remains seldomly reported. This study aimed to investigate the resistance mechanism, molecular characteristics and risk factors of E. faecalis clinical isolates from patients with UTI in China. Methods: A total of 115 non-duplicated E. faecalis clinical isolates from patients with UTI were retrospectively collected in a tertiary hospital in China and their clinical data was further analyzed. The linezolid and tedizolid susceptibility were determined by agar dilution. The resistance genes, including erm(A), erm(B), erm(C), tet(M), optrA, cfr, cfr(B), poxtA, and MLST-based housekeeping genes were investigated by PCR. Results: In 115 non-duplicated E. faecalis clinical isolates from the patients with UTI in this hospital setting, the frequency of linezolid or tedizolid-resistant/intermediate isolates were 22.61 and 13.04%, respectively, and the frequency of linezolid-resistant/intermediate E. faecalis clinical isolates carrying with erm(A) were 86%. Among the five linezolid-resistant E. faecalis strains found in this study, three optrA-positive isolates and the other two linezolid-resistant strains were G2576U genetic mutations in the V domain of the 23S rRNA genes. The ST clonality analysis indicated that 31.42% (11/35) of ST16 E. faecalis UTI isolates were not susceptible to linezolid. Moreover, the univariable analysis indicated that the high risk factors of linezolid-resistant/intermediate E. faecalis infections involved the indwelling catheter, trachea cannula catheter and the carriage of erm(A) or optrA. Furthermore, the indwelling catheter and trachea cannula catheter were demonstrated as the independent predictors of linezolid-resistant/intermediate E. faecalis strains in patients with UTI by multivariable analysis. Conclusion: Linezolid-resistant/intermediate E. faecalis associated with urinary tract infections of patients in this hospital setting from China might be explained by the high carriage frequency of optrA genes and moreover, indwelling catheter and trachea cannula should be considered as the independent predictors of linezolid-resistant/intermediate E. faecalis infections. The transmission mechanism of linezolid-resistant/intermediate E. faecalis in this hospital setting should be further studied.